Analisis Perbandingan Kinerja Keuangan Perbankan sebelum dan sesudah melakukan proses Konversi (Study kasus pada Bank NTB Syariah) - Bustamil, Bustamil; Nurwahidin, Nurwahidin (ITB AAS INDONESIA Surakarta, 2023)
After experiencing a decrease in Net Profit of 35.81% in 2017, Bank NTB finally chose to make a Conversion, namely making changes to the system and business objectives being carried out so that it was proven that there was an increase in the amount of net profit received by Bank NTB even though the amount of net profit received was still below below the net profit received in 2015 and 2016. The purpose of this study is to compare the Financial Performance of Bank NTB before and after carrying out Conversion activities. The method used in this study is comparative using a quantitative approach which aims to compare the financial performance of Bank NTB before and after conversion. The sample in this study is five quarters before converting and after converting. While the ratio used in this study is the ratio of profitability, solvency, liquidity, and asset quality. The results of this study indicate that the ROA, BOPO, CAR, and FDR variables have no differences. Meanwhile, the ROE and NPL variables show that there is a significant difference after the conversion, Bank NTB Syariah has experienced an increase in income and a decrease in the amount of problem financing.